Ethiopia and the Great Transformation - Pankhurst, Richard (Aethiopica, 2004)
The article considers Karl Polanyi’s thesis that 19th century Western capitalism was unique in basing itself on the principle of gain, as expressed by the self-regulating market system. Polanyi’s argument is examined in the light of Ethiopian historical experience, with special reference to land and labour (including slavery), agricultural production, control over trade and prices, and traditional institutions which curtail or serve as an alternative to market factors. These include church holidays, compulsory hospitality, state banquets, alms giving, and, more generally, asceticism and resignation to the Will of God.